Admissions in Japanese National Universities: The Need for Change - Ishikura, Yukiko; Kawashima, Tatsuo (International Higher Education, 2018)
Higher education institutions have undergone significant changes concerning college admissions. Leading countries for higher education, such as the United Kingdom and the United States, as well as countries in Asia such as China, Korea, and Taiwan are making changes to their higher education systems. There is also a call for change in college admissions in Japan. Japanese universities, especially national universities, have heavily relied on test scores for student selection. However, universities are currently shifting their college admissions processes toward a holistic review approach. This involves making admission decisions by assessing not only academic achievements, but also students’ backgrounds, personal experience, and potential. This task was initiated by the government in response to the changing concepts of knowledge and fairness, as well as the perceived desirability of attracting students with diverse educational backgrounds. For higher education institutions both in Japan and abroad, college admission reforms become a necessary process. Japan, where the government has the most power for making decisions, offers other countries priceless lessons about how top-down education/admission reforms are implemented or impeded.